Regiospecific formation of sugar-derived ketonitrone towards unconventional C-branched pyrrolizidines and indolizidines. Issue 29 (12th July 2019) - Massicot, Fabien; Messire, Gatien; Vallée, Alexis; Vasse, Jean-Luc; Py, Sandrine; Behr, Jean-Bernard
Abstract : The synthesis of unprecedented branched pyrrolizidines and indolizidines was accomplished via nitrone chemistry. Abstract : The synthesis of unprecedented branched pyrrolizidines and indolizidines was accomplished via nitrone chemistry. The required ketonitrone, a known intermediate usually obtained as a mixture of regioisomers, was prepared in a pure form fromd -arabinose by a sequence of oximation/reduction/oxidation steps. Nucleophilic vinylation or allylation followed by ring-closing metathesis of the corresponding N -allylpyrrolidines furnished the targeted iminosugars, which proved potent and selective inhibitors of alpha-glucosidase from rice (GH31 family).